2021
DOI: 10.1210/clinem/dgab680
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Increases Adipose Adiponectin in Pregnancy by Inhibiting Ubiquitination and Degradation: Impact of Obesity

Abstract: Context Circulating adiponectin levels are decreased in pregnant women with obesity or gestational diabetes, and this is believed to contribute to the insulin resistance and increased risk of fetal overgrowth associated with these conditions. However, the molecular mechanisms regulating adiponectin secretion from maternal adipose tissues in pregnancy are poorly understood. Objectives We tested the hypothesis that obesity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In addition, other risk factors, including prepregnancy BMI and sedentary behaviour, can be controlled. Previous research, which found that overweight and obese pregnant women had an increased risk of GD, may be attributable to inhibited insulin signalling release 46 . One meta‐analysis pointed out that sedentary behaviour during pregnancy is not clearly associated with GD, perhaps because of reporting differences and measuring challenges, 47 but weight gain resulting from sedentary behaviour and vascular factors is confirmed as being associated with GD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other risk factors, including prepregnancy BMI and sedentary behaviour, can be controlled. Previous research, which found that overweight and obese pregnant women had an increased risk of GD, may be attributable to inhibited insulin signalling release 46 . One meta‐analysis pointed out that sedentary behaviour during pregnancy is not clearly associated with GD, perhaps because of reporting differences and measuring challenges, 47 but weight gain resulting from sedentary behaviour and vascular factors is confirmed as being associated with GD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research, which found that overweight and obese pregnant women had an increased risk of GD, may be attributable to inhibited insulin signalling release. 46 One meta-analysis pointed out that sedentary behaviour during pregnancy is not clearly associated with GD, perhaps because of reporting differences and measuring challenges, 47 but weight gain resulting from sedentary behaviour and vascular factors is confirmed as being associated with GD. Pregnant women should reduce their sedentary time and maintain a low prepregnancy BMI to prevent and reduce the risk of GD.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin ubiquitination is increased in the visceral fat of obese pregnant women compared to their lean counterparts, and it is a key mechanism through which obesity curtails adiponectin secretion during pregnancy (Table 7 ). 889 …”
Section: Ubiquitinationmentioning
confidence: 99%
“…Experiments performed in 3T3L-1 adipocytes showed a potential mechanism whereby ubiquitination of adiponectin in obesity decreases adiponectin in pregnancy [ 127 ]. Ubiquitination and degradation of adiponectin appeared to be prevented by insulin and promoted by inflammation and ER stress, both of which are present in adipose tissue from obese individuals [ 127 ]. Adiponectin secretion and mRNA levels decrease in WAT as pregnancy progresses, in parallel with increasing insulin resistance [ 102 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…Although these results are promising, supplementation in rodent models often utilizes perfusion systems [ 111 ] or hydrodynamic [ 186 ] or viral gene delivery systems [ 132 , 153 ] to maintain circulating adiponectin levels due to rapid turnover of adiponectin in circulation [ 187 ]. Additionally, multiple isoforms of adiponectin exist in different ratios, with varying metabolic activity and post-translational modifications of adiponectin can impact optimal bioactivity, which may differentially impact both maternal and offspring metabolic health outcomes [ 127 ].…”
Section: Adiponectinmentioning
confidence: 99%